Toxic effects of glyphosate on the intestine, liver, brain of carp and on epithelioma papulosum cyprinid cells: Evidence from in vivo and in vitro research. (September 2022) - Cao, Xianglin; Rao, Chenyang; Cui, Han; Sun, Dandan; Li, Lulu; Guo, Suqi; Zhou, Jiameng; Yuan, Rongjie; Yang, Shuai; Chen, Jianjun
Abstract: Glyphosate (GLY) is the most widely used organophosphorus herbicide in agriculture. The present study aimed to analyze the comprehensive toxicological effects of GLY on juvenile common carp and an epithelioma papulosum cyprinid (EPC) cell line. In the in vivo experiments, exposure to GLY (5 and 15 mg/L) for 30 days induced liver inflammation and oxidative damage in common carp and changed the physical barrier of the intestine. Histopathological analysis of the intestine, liver, brain, and changes in oxidative stress biomarkers provided evidence of damage and immune system responses to GLY. Moreover, an inhibitory effect of 15 mg/L GLY on acetylcholinesterase (AChE) activity was found in the brain, which may be an important reason for the significant decrease in both swimming distance and average acceleration of common carp. Cell experiments showed that 0.65 and 3.25 mg/L GLY inhibited the viability of EPCs. Furthermore, oxidative DNA damage, mitochondrial dysfunction, and reactive oxygen species (ROS) production were observed in EPC cells following GLY exposure. Taken together, this study not only highlights the negative effects of GLY on common carp but also enriches the knowledge of the cytotoxicity mechanism to further clarify the comprehensive toxicity of GLY in common carp. Graphical abstract: Image 1 Highlights: Determination of GLY toxicity by in vivo and in vitro experiments. Substantial histopathological changes occurred in the intestine, liver, and brain. GLY induced inflammation and oxidative stress in common carp liver. GLY significantly decreased the swimming competence of common carp. GLY caused DNA damage and ROS production in EPC cells.